Implementación de un módulo didáctico de control domótico para aplicaciones prácticas en la carrera de ingeniería en electromecánica de la Universidad Técnica de Cotopaxi en el período 2013 - Cuyo Semblantes, Danilo Javier (2015)
This research is about the world level evolution of the technology in different disciplines such as: electrical, electronics, automation, telecommunications, computer science, and architecture, they have facilitated an interaction among them for contributing to design and build buildings and smart houses that they will become basic in the future in all countries. This way it originates this discipline of denominated study smart house, the same one that integrates and it communicates all the functions and home automation, allowing to the user final to interact with the system in an easy and simple way....